APLIKASI MODEL KOMPUTER DALAM ANALISIS KINERJA AKUSTIK RUANG AUDITORIUM UNIVERSITAS KRISTEN PETRA SURABAYA - Indrani, Hedy Constancia; Ekasiwi, Sri Nastiti N.; Asmoro, Wiratno A. (Institute of Research and Community Outreach - Petra Christian University, 2007)
The operation of computer program for acoustic simulation is an alternative for acoustic analysis method which is fund, time, and energy saving. ECOTECT v.5.20 is one of the computational building performance simulation integrated program with fully 3D, that is able to simulate and analyze acoustic performance of an auditorium. Accordingly it can be used as a program to design the position and area of absorption surface. With consideration to simulation activities, a computer program that makes a model of a real environment always faces the problem of simplifying a model. This problem definitely will affect the precision between the field assessment result and the parameter simulation result of a room acoustic impulse response. Verification of simulation result on the field assessment result has to be done in order to show the computer program validation to be used as a simulation tool for the next research. The simulation result shows that the Reverberation Time (RT) computation is the most equal to the field measurement result with